Taxonomy and tendencies in sustainable finance: A comprehensive literature analysis - Rodriguez-Rojas, Maria del Pilar; Clemente-Almendros, José Antonio; El Zein, Samer Ajour; Seguí-Amortegui, Luis (Frontiers in Environmental Science, 2022)
This study identifies the trends in the literature related to Sustainable Finance by means of an exhaustive literature review and a bibliometric analysis of publications taken from the Web of Science database (WoS). A search in WoS for the associated terms came up with a total of 9294 entries, showing a particularly noticeable growth in scientific production in the aftermath of the Paris Agreement of 2015. The analysis of the bibliometric networks was performed using VOSviewer (VOSviewer is a software tool for constructing and visualizing bibliometric networks), from which the analysis of key words was obtained. Using this analysis five cluster groups were identified, showing the main themes of research: Climate risk and adaptation, Low carbon energy economy or Low carbon economy, Environment, finance and governance, Low carbon emission technologies, Economic model and social cost. Further research is recommended into the themes of Low carbon energy economy and Environment, social and governance, considered key issues in the future.